2012
DOI: 10.1620/tjem.226.55
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Posterior Leukoencephalopathy Syndrome Accompanying Eclampsia: Correct Diagnosis Using Preoperative MRI

Abstract: Reversible posterior leukoencephalopathy syndrome (RPLS) is characterized by clinical symptoms such as seizures, visual disturbance, and altered mental status. It also presents abnormal findings on computed tomography (CT) and magnetic resonance imaging (MRI) indicating cerebral edema in the white matter of the occipital, temporal, and parietal lobes. Both the clinical symptoms and abnormal imaging findings can be reversed by controlling blood pressure or treating the underlying condition including infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
3
12
0
4
Order By: Relevance
“…Both these patients went on to develop seizures on post natal day 2. This finding is consistent with the findings of previous studies 20 in which investigators have shown that endothelial damage in patients with preeclampsia-eclampsia is not a result of hypertension but actually precedes substantial blood pressure increases. The endothelial dysfunction experienced by these patients is more likely related to circulating endothelial toxins or antibodies against the endothelium.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Both these patients went on to develop seizures on post natal day 2. This finding is consistent with the findings of previous studies 20 in which investigators have shown that endothelial damage in patients with preeclampsia-eclampsia is not a result of hypertension but actually precedes substantial blood pressure increases. The endothelial dysfunction experienced by these patients is more likely related to circulating endothelial toxins or antibodies against the endothelium.…”
Section: Discussionsupporting
confidence: 93%
“…[17][18][19] However PRES has been demonstrated in women with severe preeclampsia without seizure, and it has been demonstrated to precede eclamptic convulsion. 20 In our study, out of 21 patients with positive MRI findings 3 patients were diagnosed with severe Preeclampsia. Two of these three (66.66%) patient developed seizures on postnatal day 2.…”
Section: Discussionmentioning
confidence: 58%
“…Clinically, PRES presents with headache, seizures, encephalopathy, visual disturbances and focal neurological symptoms 19. As the name suggests, reversibility of these symptoms is one of the hallmarks of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 Nearly half of the neurological events related to pregnancy consist of intracerebral hemorrhage, venous thrombosis, subarachnoid hemorrhage and infarction, and the remainder are pregnancy related encephalopathy. 2 Here, we describe a patient with posterior reversible encephalopathy syndrome (PRES) and intracerebral hemorrhage that had occurred secondary to HELLP syndrome.…”
mentioning
confidence: 99%
“…PRES syndrome was first described by Hinchey et al in 1996 2. Symptoms of PRES in the general population comprise clinical seizures (87%), encephalopathy (92%), visual symptoms (39%), Axial CT (a)-(c) and MR (d)-(f) images on the 2nd day the hematoma in the right hemisphere, density and signal abnormalities expanded, and became more evident, contrarily subarachnoid hemorrhage disappeared.…”
mentioning
confidence: 99%